Pathway Analysis for Biocrystallisation and Biodeposition of Pd(II) and Pt(II) Metals by Sulfate-Reducing Bacteria - Chirwa, Evans M.N. (University of Pretoria, 2021)
Dissertation (MSc ((Applied Science) (Water Utilisation)))--University of Pretoria, 2021.